Experts' review: the emerging roles of romiplostim in immune thrombocytopenia (ITP). (2nd November 2021) - Chen, Frederick; McDonald, Vickie; Newland, Adrian
ABSTRACT: Introduction: The management of ITP has in recent years been transformed from reliance on immunosuppressants and splenectomy to targeted therapy with thrombopoietin receptor agonists (TPO-RA) that directly stimulate platelet production in the bone marrow. This has reduced the long-term infective complications and toxicities associated with the use of potent immunosuppressants and splenectomy. The welltolerated romiplostim, itself a novel drug construct called peptibody, has established itself, alongside other TPO-RA as the preferred 2nd line therapy in major international guidelines on treatment of ITP. Areas covered: This review summarizes the data from early licensing trials of romiplostim and discusses the real-world experience to date, the unexpected emerging data on treatment-free long-term remission achieved using TPO-RA, and the case for its early introduction in the therapeutic pathway. The emerging risk of thrombosis is also discussed. Expert opinion: The use of romiplostim and other TPO-RA will be increasingly brought forward in the management pathway of ITP with the prospect of modifying the long-term outcome of the disease by increasing sustained treatment-free remission. With the prospect of several new targeted therapies been introduced into clinical practice, TPO-RA will likely be a key component of future combination therapies for difficult cases.